Apprenticeship review Malta : in pursuit of quality and relevance: revitalising apprenticeship - (:unkn) unknown (Publications Office of the European Union, 2015)
"The report explores the major features, strengths and weaknesses of apprenticeship in Malta (in place since the early 1990s). The analyses also show how the Malta College of Arts and Technology has been making efforts over the past year to improve the system and boost participation of learners and companies. It is the final report of the thematic country review on apprenticeships which Cedefop carried out in Malta between May 2014 and April 2015 at the request of the Ministry of Education and Employment. The analyses largely rely on information collected from different categories of stakeholders at different levels; they are accompanied by suggestions for action and may contribute to ongoing apprenticeship reform. It is up to the national authorities whether, and how, to take them further." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Bildungsreform; Malta